Methods of Detection Anthelmintic Resistance in Sheep and Goats - Haryuningtyas, Dyah; ., Beriajaya (Indonesian Bulletin of Animal and Veterinary Sciences, 2002)
Anthelmintic resistance to gastrointestinal nematode of sheep and goats has been reported world wide to all of broad spectrum anthelmintic types currently available, such as benzimidazoles, levamizole and ivermectin. In South-East Asia anthelmintic resistance to small ruminants was reported in Malaysia, Thailand and Philippines. In Indonesia resistances to albendazole have been reported from sheep farm in Bogor. With regard to resistance cases, early detection for anthelmintic resistance on sheeps and goats to spesific types of anthelmintic that commonlly used are required to plan rationale strategic control program. Detection methods for anthelmintic resistance are Fecal Egg Count Reduction Test (FECRT), Egg Hatch Assay (EHA) and Larval Development Assay (LDA). LDA is an in vitro assay to detect anthelmintic resistant in the major of gastrointestinal nematodes on sheep and goats that have just been introduced in Indonesia. This paper explains the comparison of three detection methods and goodness of LDA compared with other two methods. Â  Key words: Anthelmintic resistance, sheep, goat, Fecal Egg Count Reduction Test (FECRT), Egg Hatch Assay (EHA), LarvalDevelopment Assay (LDA)